Pelatihan Pengembangan Multimedia bagi Calon Guru PAUD Di FKIP Universitas Mataram - Gunawan, Gunawan; Astini, Baik Nilawati; Rahchmayani, Ika; Noerhasanah, Noerhasanah (Indonesian Publication Center, 2023)
The advancement of technology demands that prospective Early Childhood Education (ECE) teachers possess competencies in multimedia development to create engaging and effective learning experiences. This community service aimed to enhance these competencies through a four-stage training program: (1) participant registration and data collection, (2) theoretical and conceptual introduction to multimedia, (3) guided media creation with 11 relevant themes, and (4) evaluation and discussion of media products. Thirty 5th-semester students participated in the training. Evaluation results indicated the success of the training in developing skills and motivating participants. This activity contributes positively to preparing prospective ECE teachers to meet the demands of the evolving educational landscape.